Chyloperitoneum signifying late bowel obstruction following gastric clipping with proximal jejunal bypass: A case report - Chih Hung Hsu; Jin Ruei Yang; Fang Ling Chiu; Jan Sing Hsieh (Journal of Minimal Access Surgery, 2024)
Chyloperitoneum (CP) is a rare complication after bariatric surgery. We present a 37-year-old female with CP caused by a bowel volvulus following a gastric clipping with proximal jejunal bypass for morbid obesity. An abdominal CT image of a mesenteric swirl sign and abnormal triglyceride level of ascites fluid can confirm the diagnosis. In this patient, laparoscopy demonstrated dilated lymphatic ducts caused by a bowel volvulus resulting in the exudation of chylous fluid into the peritoneal cavity. After the reduction of bowel volvulus, she made an uneventful recovery with complete resolution of the chylous ascites. The presence of CP could indicate a situation of small bowel obstruction in patients with a history of bariatric surgery.